The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1093/annonc/mdx699
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Grade Index predicts postoperative clinical outcome in patients with soft-tissue sarcoma

Abstract: GGI refines the prediction of MFS in operated STS and might improve the tailoring of adjuvant chemotherapy. Further clinical validation is warranted in larger retrospective, then prospective series, as well as the functional validation of relevant genes that could provide new therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Nevertheless, there is no data on the prognostic value of baseline Hb levels and outcomes in sarcomas. The increasingly widespread use of molecular biology is now promoting a better understanding of the complexity of STS and making it possible to identify predictive signatures of the risk of metastatic recurrence in localized STS [51,52]. In vitro studies have suggested that cells with a deficient homologous recombination DNA repair pathway have a higher sensitivity to trabectedin [53], and retrospective studies have shown that BRCA1 (breast cancer gene 1) status may be predictive of trabectedin efficacy [54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no data on the prognostic value of baseline Hb levels and outcomes in sarcomas. The increasingly widespread use of molecular biology is now promoting a better understanding of the complexity of STS and making it possible to identify predictive signatures of the risk of metastatic recurrence in localized STS [51,52]. In vitro studies have suggested that cells with a deficient homologous recombination DNA repair pathway have a higher sensitivity to trabectedin [53], and retrospective studies have shown that BRCA1 (breast cancer gene 1) status may be predictive of trabectedin efficacy [54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that isolated gains of 3p in ChRCC was correlated to sarcomatoid differentiation while gain of chromosome 21 was correlated to poor prognosis 34,35 . Moreover, since it is usually described that tumors showing segmental unbalances may have a higher aggressiveness than tumors showing gains or losses of whole chromosomes, 36,37 this raises the issue of histopathological features related to these segmental quantitative alterations. However, Sperga et al 26 did not observe any correlation of a combination of gains and losses in a series of 37 ChRCC to histological features or to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This variance in treatment response is linked with both intratumoral and intertumoral genomic heterogeneity, with subclonal tumor populations with distinct gene expression profiles that may correspond to their response to various treatment modalities. 4,13,[16][17][18][19] These findings provide insight into the potential to improve outcome by applying radiation dose heterogeneously, or "dose painting," based on the distinct subclonal populations throughout the tumor, rather than the typical homogenous dose distributions that are currently used.…”
Section: Genomicsmentioning
confidence: 99%